The influence of psychological capital on innovative work behavior in islamic bank employees X - Rezky, Alina Tivta (Journal of Economic, Business & Accounting Research, 2024)
Background: In the face of intense business competition, organizations need continuous innovation in technology and services to remain competitive. This study explores how psychological capital—including self-efficacy, optimism, hope, and resilience—influences innovative work behaviour in the Islamic banking sector in Indonesia. This study aims to look at the effect of psychological capital on innovative work behaviors in employees of Bank Syariah X. Method: The sample used in the study was 135 employees working at Bank Syariah X. Innovative Work Behavior was measured using Innovative Work Behavior Indonesia version (2014). Psychological capital was measured using Psychological capital Questionnaire-24 (PCQ-24) (2007) with reliability coefficient 0.87. Findings: The results showed that two components of psychological capital significantly influence the behavior of innovative work, namely self efficacy (β = 0.33, R2 = 0.21, p = 0.00) and hope (β = 0.21, R2 = 0.03, p = 0.00). Conclusion: This suggests that the components of self efficacy was the biggest influence on the innovative work behavior among employees who work at the Bank Syariah X. Novelty/Originality of this study: This research framework provides practical and measurable strategies that can be implemented by HR managers in the Islamic banking sector to drive innovation, improve employee performance, and ultimately enhance organizational competitiveness in the dynamic financial industry.